Fe-POM/attapulgite composite materials: Efficient catalysts for plastic pyrolysis. Issue 9 (September 2022) - Attique, Saira; Batool, Madeeha; Goerke, Oliver; Abbas, Ghayoor; Saeed, Faraz Ahmad; Din, Muhammad Imran; Jalees, Irfan; Irfan, Ahmad; Gregory, Duncan H; Tufail Shah, Asma
This article describes the catalytic cracking of low-density polyethylene over attapulgite clay and iron substituted tungstophosphate/attapulgite clay (Fe-POM/attapulgite) composite materials to evaluate their suitability and performance for recycling of plastic waste into liquid fuel. The prepared catalysts enhanced the yield of liquid fuel (hydrocarbons) produced in cracking process. A maximum yield of 82% liquid oil fraction with a negligible amount of coke was obtained for 50% Fe-POM/attapulgite composite. Whereas, only 68% liquid oil fractions with a large amount of solid black residue was produced in case of non-catalytic pyrolysis. Moreover, Fe-POM/attapulgite clay composites showed higher selectivity towards lower hydrocarbons (C5 –C12 ) with aliphatic hydrocarbons as major fractions. These synthesised composite catalysts significantly lowered the pyrolysis temperature from 375°C to 310°C. Hence, recovery of valuable fuel oil from polyethylene using these synthesised catalysts suggested their applicability for energy production from plastic waste at industrial level as well as for effective environment pollution control.